Dihydrolipoyl dehydrogenase as a source of reactive oxygen species inhibited by caloric restriction and involved in Saccharomyces cerevisiae aging - Tahara, Erich B.; Barros, Mario H.; Oliveira, Graciele A.; Netto, Luis E. S.; Kowaltowski, Alicia J. (Federation Amer Soc Exp Biol, 2007)
Replicative life span in Saccharomyces cerevisiae is increased by glucose (G1c) limitation [ calorie restriction (CR)] and by augmented NAD(+). Increased survival promoted by CR was attributed previously to the NAD(+)-dependent histone deacetylase activity of sirtuin family protein Sir2p but not to changes in redox state. Here we show that strains defective in NAD(+) synthesis and salvage pathways (pnc1 Delta, npt1 Delta, and bna6 Delta) exhibit decreased oxygen consumption and increased mitochondrial H2O2 release, reversed over time by CR. These null mutant strains also present decreased chronological longevity in a manner rescued by CR. Furthermore, we observed that changes in mitochondrial H2O2 release alter cellular redox state, as attested by measurements of total, oxidized, and reduced glutathione. Surprisingly, our results indicate that matrix-soluble dihydrolipoyl-dehydrogenases are an important source of CR-preventable mitochondrial reactive oxygen species (ROS). Indeed, deletion of the LPD1 gene prevented oxidative stress in npt1 Delta and bna6 Delta mutants. Furthermore, pyruvate and alpha-ketoglutarate, substrates for dihydrolipoyl dehydrogenase-containing enzymes, promoted pronounced reactive oxygen release in permeabilized wild-type mitochondria. Altogether, these results substantiate the concept that mitochondrial ROS can be limited by caloric restriction and play an important role in S. cerevisiae senescence. Furthermore, these findings uncover dihydrolipoyl dehydrogenase as an important and novel source of ROS leading to life span limitation.
Keywords: free radicals; yeast; senescence; alpha-ketoglutarate dehydrogenase